“And Then We’ll Just Check If It Suits Us” – Cognitive-Affective Maps of Social Innovation in Early Childhood Education - Luthardt, Jasmin; Schröder, Tobias; Hildebrandt, Frauke; Bormann, Inka (Frontiers in Education, 2020)
The idea of a simple execution of an innovation invented by other actors than those who are expected to apply it, is a truism. We assume, however, in this paper the idea of a discursive production of knowledge on the application of an innovation across different levels of the education system. We aim to shed light on an innovation’s ‘journey’ from educational policy over training providers to teams of professionals in early childhood education and care (ECEC). By investigating knowledge and emotions associated with the introduction of an intended innovation using the example of “stimulation interactions” in day care-centers, the paper contributes to research on the transfer of innovations in education. To better understand challenges occurring during the transfer of innovations, we triangulate methods from discourse theory (coding techniques based on GTM) and cognitive science, namely cognitive-affective mapping (according to the scholarly conventions). The data corpus includes educational plans (N=2), in-service training programs (N=123) and group discussions of pedagogical teams (N=6) who participated in an in-service training on the subject ‚stimulating interaction‘. Findings underline that similar messages from the inventors on the educational policy level are received and processed heterogeneously by the teams of pedagogues as a result of their preexisting views, routine practices and experiences with intended innovations through in-service trainings. Besides, a diffuse mixture of competing and contradictory information is communicated to the professionals and, hence, collides with the in-service training providers’ and educational policy actors’ expectations on the processing of the intended innovation. Specific knowledge elements and their valences are diametrically opposed to each other. Dissonances like these are considered as obstacles to social innovation. The obstacles are caused by the lack of a ‘common language’ beyond all levels. Hence, policy-makers and in-service-training providers should anticipate the supportive as well as competing knowledge-emotional complexes of professionals and take these into account when communicating an intended innovation.